The language of dying - Pinborough, Sarah, 1972- (Jo Fletcher Books, 2016)
"In this emotionally gripping, genre-defying novella from Sarah Pinborough, a woman sits at her father's bedside, watching the clock tick away the last hours of his life. Her brothers and sisters--she is the middle child of five--have all turned up over the past week to pay their last respects. Each is traumatized in his or her own way, and the bonds that unite them to each other are fragile--as fragile perhaps as the old man's health. With her siblings all gone, back to their self-obsessed lives, she is now alone with the faltering wreck of her father's cancer-ridden body. It is always at times like this when it--the dark and nameless, the impossible, presence that lingers along the fringes of the dark fields beyond the house--comes calling. As the clock ticks away in the darkness, she can only wait for it to find her, a reunion she both dreads and aches for."--